Estimation of the Lateral Ventricles Volumes from a 2D Image and Its Relationship with Cerebrospinal Fluid Flow. - Bader, Chaarani; Cyrille, Capel; Jadwiga, Zmudka; Joel, Daouk; Fichten, Anthony; Catherine, Gondry-Jouet; Roger, Bouzerar; Olivier, Balédent (BioMed Research International, 2013)
Purpose. This work suggests a fast estimation method of the lateral ventricles volume from a 2D image and then determines if this volume is correlated with the cerebrospinal fluid flow at the aqueductal and cerebral levels in neurodegenerative diseases. Materials and Methods. FForty-five elderly patients suffering from Alzheimer's disease (19), normal pressure hydrocephalus (13), and vascular dementia (13) were involved and underwent anatomical and phase contrast MRI scans. Lateral ventricles and stroke volumes were assessed on anatomical and phase contrast scans, respectively. A common reference plane was used to calculate the lateral ventricles' area on 2D images. Results. The largest volumes were observed in hydrocephalus patients. The linear regression between volumes and areas was computed, and a strong positive correlation was detected (R² = 0.9). A derived equation was determined to represent the volumes for any given area. On the other hand, no significant correlations were detected between ventricles and stroke volumes (R² ≤ 0.15). Conclusion. Lateral ventricles volumes are significantly proportional to the 2D reference section area and could be used for patients' follow-up even if 3D images are unavailable. The cerebrospinal fluid fluctuations in brain disorders may depend on many physiological parameters other than the ventricular morphology.